Amonium and Nitrate Of Soil In Relation To Water Table Fluctuation At The Tidal Rice Fields - Warsito Warsito (Program Pascasarjana Universitas Sriwijaya, 2018)
The reclaimed lowlands of Indonesia with the respective of 256 hectares of secondary block consist of 16 hectares of tertiary blocks, were used for rice plant production. Paddy was planted during the rainy season of November to February. It was followed by water melon plant in March to May. Then corn was growed in the dry season of June to September finally. Fluctuations of water table in the farm is very crucial in determining the cropping calender. Water management with free drainage approach is influenced by tidal water movement into the tertiary canals bordering the farmers fields. A constant water retention -10 cm below the canal bank has increased the water table in the farm from -10 cm to +20 cm. Water retention (controlled drainage) mode was applied by the farmers especially during the rice growing period. The release of water in the canal to a depth of -50 cm below the canal bank had lowered the water table level to -20 cm. During almost 200 days of experimental work, soil and water samples were taken by 11 times. The content of NO3-, NH4+and pH of the soil sample and be analyzed in relation to the water table fluctuation. Groundwater level does not show the effect on nitrate release on the urea application stocked. however, on the high ground water level it appears to be more in control of ammonium release compared to the ground water level of -20 cm.